2000
DOI: 10.1152/ajpendo.2000.279.5.e1039
|View full text |Cite
|
Sign up to set email alerts
|

Lipid oxidation is reduced in obese human skeletal muscle

Abstract: The purpose of this study was to discern cellular mechanisms that contribute to the suppression of lipid oxidation in the skeletal muscle of obese individuals. Muscle was obtained from obese [body mass index (BMI), 38.3 +/- 3.1 kg/m(2)] and lean (BMI, 23.8 +/- 0.9 kg/m(2)) women, and fatty acid oxidation was studied by measuring (14)CO(2) production from (14)C-labeled fatty acids. Palmitate oxidation, which is at least partially dependent on carnitine palmitoyltransferase-1 (CPT-1) activity, was depressed (P <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
468
5
10

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 524 publications
(521 citation statements)
references
References 32 publications
29
468
5
10
Order By: Relevance
“…Mitochondrial function is not impaired in type 2 diabetes Several studies have provided evidence of mitochondrial dysfunction in skeletal muscle of type 2 diabetic, prediabetic and obese participants [1,8,9,11,12,36]. In our study the measure of oxidative capacity and of citrate synthase activity clearly argues against mitochondrial or cellular dysfunction as a confounding variable in lipid accumulation of muscle from type 2 diabetic patients.…”
Section: Discussionsupporting
confidence: 44%
“…Mitochondrial function is not impaired in type 2 diabetes Several studies have provided evidence of mitochondrial dysfunction in skeletal muscle of type 2 diabetic, prediabetic and obese participants [1,8,9,11,12,36]. In our study the measure of oxidative capacity and of citrate synthase activity clearly argues against mitochondrial or cellular dysfunction as a confounding variable in lipid accumulation of muscle from type 2 diabetic patients.…”
Section: Discussionsupporting
confidence: 44%
“…Kim et al [32] showed that CS activity was significantly reduced in the vastus lateralis of obese subjects, suggesting that the low mitochondrial content in the skeletal muscle of these subjects contributed to their decrease in muscle oxidative capacity.…”
Section: Discussionmentioning
confidence: 99%
“…), 1 mmol/l carnitine and 12.5 mmol/l HEPES. Incubation medium was then transferred to a 24 dual-well Teflon trapping plate [37] and the reaction terminated by adding 70% perchloric acid (wt/vol.). During 1 h incubation at 25°C, 14 CO 2 was trapped in 1 mol/l sodium hydroxide and quantified by liquid scintillation counting.…”
Section: Exercise Intervention and [ 18 F]fluorodeoxyglucose Petmentioning
confidence: 99%